Development of English Language Materials Based on Teaching Modules to Improve Writing Skills - Devi Wulan Dari; Nurhanna Harahap; Shopiah Anggraini Rambe (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
English language skills are now an important need in the era of globalisation. In addition to facilitating international communication, English proficiency also opens access to various sources of science and technology and encourages participation in global innovation. English is not only a personal advantage, but also a valuable asset for groups and countries. With good proficiency, a person can make a major contribution to facing global challenges and strengthening international cooperation. English also helps understand and respond to world developments. This study is development research using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to create a narrative text learning module. In the Analysis stage, researchers identified student difficulties related to teaching materials. During the Design stage, a module was created containing narrative text materials, including structure and types. The Development stage involved building the module and validating it with subject matter and media experts. The Implementation stage tested the module with students. The Evaluation stage aims to assess the extent to which the module learning media are effective in supporting the learning process. The module received a 90% validity score from material experts and 87.5% from media experts, both categorised as very valid. The module's effectiveness, based on an n-gain score of 0.70, was classified as high. Therefore, the developed module is considered valid, effective, and suitable for use in teaching narrative texts in English language learning.